Development of augmented reality learning media based on assemblr studio web in ecosystem material - Nengsih Nengsih; Anandita Eka Setiadi Eka; Ari Sunandar (University of Muhammadiyah Malang, 2023)
Augmented Reality displays realistic-looking 3D animations. Learning media utilizing Augmented Reality can assist students in comprehending Biology education, particularly ecosystem materials, with greater concreteness. This study reports the development of Augmented Reality learning media based on Assemblr Studio Web, known for its validity and positive response from students. The research employs the Research and Development (R&D) approach with a 3D modification development model derived from the 4D model developed by Thiagarajan. The Augmented Reality learning media based on Assemblr Studio Web received highly valid assessments from subject matter experts (85.18%), media experts (90%), and language experts (80.83%). In a small-scale trial involving 27 students, a response rate of 78.51% (positive) was recorded, while in a large-scale trial with 63 students, the response rate was 76.4% (positive). It is concluded that the developed Augmented Reality learning media based on Assemblr Studio Web is highly suitable for use in the learning process and has received positive feedback from students.